Impact of Financial Regulations on Insurance Company Profitability in Morocco - Ben, Rachid (Journal of Statistics and Actuarial Research, 2024)
Purpose: The aim of the study was to analyze the impact of financial regulations on insurance company profitability in Morocco. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Financial regulations in Morocco exert a significant influence on insurance company profitability by enforcing rigorous risk management practices and ensuring compliance with solvency and investment guidelines. These regulations foster market stability, promote fair competition, and encourage insurers to innovate in product development and operational efficiency. Adapting to regulatory changes and economic conditions is essential for insurers seeking to optimize processes and investments, thereby enhancing profitability through strategic management and innovation. Unique Contribution to Theory, Practice and Policy: Agency theory, transaction cost economics & resource dependency theory may be used to anchor future studies on analyze impact of financial regulations on insurance company profitability in Morocco. Encourage insurers to adopt adaptive risk management strategies that align with regulatory requirements while optimizing profitability. Advocate for greater harmonization of regulatory standards across jurisdictions to minimize compliance complexities for insurers operating in multiple markets.